SEG Technical Program Expanded Abstracts 2005 2005
DOI: 10.1190/1.2148199
|View full text |Cite
|
Sign up to set email alerts
|

Green's function representations for seismic interferometry

Abstract: The term seismic interferometry refers to the principle of generating new seismic responses by crosscorrelating seismic observations at different receiver locations. The first version of this principle was derived by Claerbout ͑1968͒, who showed that the reflection response of a horizontally layered medium can be synthesized from the autocorrelation of its transmission response. For an arbitrary 3D inhomogeneous lossless medium it follows from Rayleigh's reciprocity theorem and the principle of time-reversal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
201
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(201 citation statements)
references
References 14 publications
0
201
0
Order By: Relevance
“…We follow the derivation of SI in [10]. Let x i for 1 ≤ i ≤ N be the location of sources, ω the angular frequency, andĜ(x A , x i , ω) andĜ(x B , x i , ω) the Fourier transforms of the signal for a source located at x i and recorded at receivers A and B, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We follow the derivation of SI in [10]. Let x i for 1 ≤ i ≤ N be the location of sources, ω the angular frequency, andĜ(x A , x i , ω) andĜ(x B , x i , ω) the Fourier transforms of the signal for a source located at x i and recorded at receivers A and B, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent theoretical studies have shown that the cross-correlation of diffuse wavefields can provide an estimate of the Green's functions between receivers Lobkis 2001, 2004;Snieder 2004;Wapenaar 2004;Wapenaar and Fokkema 2006). Using coda waves of seismic events (Campillo and Paul 2003) and long seismic noise sequences (Shapiro and Campillo 2004), it was confirmed that it is possible to estimate the Rayleigh wave component of Green's functions between two stations by the cross-correlation of simultaneous recordings, a method now generally referred to as seismic interferometry.…”
Section: Recommendationsmentioning
confidence: 95%
“…Only closed systems have, in general, normal modes. Alternative derivations, also valid for open systems of acoustic waves, have been developed using time-reversal invariance (Derode et al 2003a, b;Bakulin and Calvert 2004), representation theorems (Wapenaar et al 2005;Wapenaar and Fokkema 2006), and the summation of random incident plane waves (Weaver and Lobkis 2005). The derivation based on representation theorems has been extended to elastic waves (Wapenaar 2004).…”
Section: Correlation Approachmentioning
confidence: 98%